Xyloglucan Biosynthesis: From Genes to Proteins and Their Functions - Julian, Jordan D.; Zabotina, Olga A. (Frontiers in Plant Science, 2022)
The plant’s recalcitrant cell wall is composed of numerous polysaccharides, including cellulose, hemicellulose, and pectin. The most abundant hemicellulose in dicot cell walls is xyloglucan, which consists of a β-(1->4) glucan backbone with α-(1->6) xylosylation producing an XXGG or XXXG pattern. Xylose residues of xyloglucan are branched further with different patterns of arabinose, fucose, galactose, and acetylation that varies between species. Although xyloglucan research in other species lag behind A. thaliana, significant advances have been made into the agriculturally relevant species Oryza sativa and Solanum lycopersicum, which can be considered model organisms for XXGG type xyloglucan. In this review, we will present what is currently known about xyloglucan biosynthesis in A. thaliana, O. sativa, and S. lycopersicum and discuss the recent advances in the characterization of the glycosyltransferases involved in this complex process and their organization in the Golgi.